Application of a JEG-3 organoid model to study HLA-G function in the trophoblast - Zhuang, Bai-Mei; Cao, Dan-Dan; Liu, Xiao-Feng; Wang, Li; Lin, Xiao-Li; Duan, Yong-Gang; Lee, Cheuk-Lun; Chiu, Philip C. N.; Yeung, William S. B.; Yao, Yuan-Qing (Frontiers in Immunology, 2023)
The human placenta is a unique temporary organ with a mysterious immune tolerance. The formation of trophoblast organoids has advanced the study of placental development. HLA-G is uniquely expressed in the extravillous trophoblast (EVT) and has been linked to placental disorders. With older experimental methodologies, the role of HLA-G in trophoblast function beyond immunomodulation is still contested, as is its role during trophoblast differentiation. Organoid models incorporating CRISPR/Cas9 technology were used to examine the role of HLA-G in trophoblast function and differentiation. JEG-3 trophoblast organoids (JEG-3-ORGs) were established that highly expressed trophoblast representative markers and had the capacity to differentiate into EVT. CRISPR/Cas9 based on HLA-G knockout (KO) significantly altered the trophoblast immunomodulatory effect on the cytotoxicity of natural killer cells, as well as the trophoblast regulatory effect on HUVEC angiogenesis, but had no effect on the proliferation and invasion of JEG-3 cells and the formation of TB-ORGs. RNA-sequencing analysis further demonstrated that JEG-3 KO cells followed similar biological pathways as their wild-type counterparts during the formation of TB-ORGs. In addition, neither HLA-G KO nor the exogenous addition of HLA-G protein during EVT differentiation from JEG-3-ORGs altered the temporal expression of the known EVT marker genes. Based on the JEG-3 KO (disruption of exons 2 and 3) cell line and the TB-ORGs model, it was determined that HLA-G has a negligible effect on trophoblast invasion and differentiation. Despite this, JEG-3-ORG remains a valuable model for studying trophoblast differentiation.